Новые циклопы (Crustacea, Cyclopidae) для фауны Украины - Монченко, В.И.; Сопова, Е.М. (Вестник зоологии, 1984)
Изучение материала, собранного Е. М. Соповой в колодцах Крымской обл. в 1984 г., позволило обнаружить два ранее неизвестных в фауне Украинской ССР вида циклопов. Описываемый материал хранится в Институте зоологии им. И. И. Шмальгаузена АН УССР (Киев). Eucyclops persistens tauricus ssp. n. differs from the nominate subspecies (brackish mouth of two Caucasian rivers near the Black Sea) in indices of dorsal and middle inner furcal setae in females (11.6-15.7 versus 9.7-13.1) and in six weakly transgressed indices in males. Type-locality: Crimea wells in Zarechnoye and Simferopol. Acanthocyclops venustus from Crimea is redescribed with special reference to mouthpars. It is the southernmost find in the USSR (other known localities: Karelian ASSR, Rybinsk reservoir, Norilsk, Yana river basin).